South China Botanical Garden of Chinese Academy of Sciences - Tkachenko Kirill (Hortus Botanicus, 2017)
The article is based on the author's personal experience of visiting the South China Botanical Garden in Guangzhou City. The Garden collections of plants contain about 14 thousand taxa. The basis of the collections are tropical plant species. Many rare and endangered plant species are preserved in the Garden. The Garden is currently a part of the South China Institute of Botany, Chinese Academy of Sciences. Herbarium consists of 1 100 000 sheets. The Garden holds many educational activities and serves as a base for diverse scientific research.